2002
DOI: 10.1034/j.1600-0773.2002.900306.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P‐450 Enzymes Contributing to Demethylation of Maprotiline in Man

Abstract: From case reports of patients treated with the tetracyclic antidepressant drug maprotiline, it appears that this drug is subject to polymorphic metabolism. Thus, we studied formation of the major maprotiline metabolite desmethylmaprotiline to identify the human cytochrome P-450 enzymes (CYP) involved. In incubations with human liver microsomes from two different donors, the substrate maprotiline was used at five different concentrations (5 to 500 mM). For selective inhibition of CYPs, quinidine (0.5-50 mM; CYP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…a. Maprotiline. Maprotiline is metabolized to desmethylmaprotiline (active) mainly (ϳ80% in EMs) by CYP2D6 (Brachtendorf et al, 2003). Other metabolites (e.g., hydroxy derivatives) (Breyer-Pfaff et al, 1985) may also be active.…”
Section: Doxepin (Tertiary)/desmethyldoxepin (Secondary)mentioning
confidence: 99%
“…a. Maprotiline. Maprotiline is metabolized to desmethylmaprotiline (active) mainly (ϳ80% in EMs) by CYP2D6 (Brachtendorf et al, 2003). Other metabolites (e.g., hydroxy derivatives) (Breyer-Pfaff et al, 1985) may also be active.…”
Section: Doxepin (Tertiary)/desmethyldoxepin (Secondary)mentioning
confidence: 99%
“…All the patients had received risperidone for more than 1 week before the study. Fifty-eight patients (65.2%) also received co-medications that are reported to be CYP2D6-dependent: levomepromazine (Suzuki et al, 1997), chlorpromazine (Suzuki et al, 2001), bromperidol (Suzuki et al, 1997), haloperidol (Suzuki et al, 2001), olanzapine (Gossen et al, 2002), paroxetine (Spina et al, 2001), fluvoxamine (D'Arrigo et al, 2005), amitriptyline (Castberg et al, 2005), maprotiline (Brachtendorf et al, 2002), terbinafine (Castberg et al, 2005, cimetidine (Madeira et al, 2004), mexiletine (Hara et al, 2005). The patients' compliance was confirmed by the nursing staff.…”
Section: Subjectsmentioning
confidence: 97%
“…It has been reported that TCAs are metabolized by several CYP isozymes [13][14][15][16][17][18][19] Since TCAs inhibit CYP2D6-mediated enzyme activity26,27), it is not surprising that numerous interactions between TCAs and commonly used drugs, which are categorized as substrates of CYP2D6, has been observed. However, the exact inhibitory potency of TCAs on CYP2D6 has not been extensively studied.…”
Section: Discussionmentioning
confidence: 99%
“…Competitive inhibition was observed with CYP2D6 and 3A4, while only a marginal effect was observed with CYP1A2, 2C9 and 2C19. In general, TCAs are mainly metabolized to N-demethylated and hydroxylated forms [13][14][15][16][17][18][19] . The hydroxylation reaction is mainly mediated by CYP2D613, 14,17,19), and several CYPs are involved in the N-demethylation 15"6,1 8,19) Venkatakrishnan et al reported that nortiptyline, classified in the same TCA group as amoxapine, is metabolized to 10-hydroxynortriptyline by CYP2D6 with an apparent Km value of 2.1 pM and CYP3A4 with an apparent Km value of 37.4 pM13).…”
Section: Discussionmentioning
confidence: 99%